DEVELOPMENT FEASIBILITY OF CRACKER MSMEs IN BOGOR CITY (Case Study : Simping Beras Kencur Teteh Sari Business) - Pandu Ahmad Ihsan Rabbani; Nia Rosiana (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2022)
The Biopharma plant processing business has great potential, especially in this pandemic. Cutcherry is a biopharmaceutical plant that has many health benefits. Teteh Sari is a cutcherry cracker business with a development plan in the form of house building production and procurement of production machinery and equipment. This research was conducted to analyze the feasibility of the development plan for the Teteh Sari cutcherry cracker business, which will be carried out. Feasibility analysis includes non-financial and financial aspects. As a result of the non-financial aspect, the business development plan is feasible to run based on the feasibility score for each non-financial aspect above 50 percent. The analysis of the financial aspect results obtained an NPV value of IDR 220.345.204, an IRR of 80,42 percent, a Net B/C of 6,44, and a Payback Period of 2,85 years; the business development plan is financially feasible because it passes the eligibility criteria. The switching value analysis shows that the business is sensitive to a decrease in the amount of production.